INTENSIVE CITIZENSHIP EDUCATION IN NIGERIAN SCHOOLS: A CURE FOR THE MOUNTING MORAL FAULTS AMONG YOUTHS - FAN, FAN AKPAN; SAMUEL, RUTH IWANGER (Innovare Journal of Education, 2021)
Nigeria’s social life is characterized by moral faults, naked greed, dishonesty and corruption even among the youths. This paper therefore calls for an intensive citizenship education for them. This education is the deliberate inculcation of social and cultural attitudes, knowledge and skills that enable individuals to become socially and politically integrated within the society. The focus of such education should be the constitution, government and politics, national symbols, political leadership and followership, local and state structures, discipline in national life, constituted authority, human rights use, care of public property, traditional institutions, and the rights, obligations and duties of citizens. The paper cautions the youths to shun vices and learn to serve, care for, share with as well as invest in others. They should seek what they can do for the country and not what the country can do for them.